Gotham City sirens songs of the sirens - Dini, Paul; Bedard, Tony; March, Guillem 1979- (DC Comics, 2010)
Catwoman, Poison Ivy, and Harley Quinn are tired of playing by other people's rules. As their alliance with the Riddler continues, they will do anything to find out which villain is targeting them for death.